Educating global citizens : a study of interaction between NGOs and schools in Finland - Henriksson, Heidi; Åbo Akademis förlag (Åbo Akademis förlag, 2022)
Abstrakt.
Keywords: globaalikasvatus; kansalaisjärjestöt; koulut; peruskoulu; yläkoulu; lukio; opetussuunnitelmat; oppimateriaali; opettajankoulutus; täydennyskoulutus; kampanjat; työpajat; maailmankansalaisuus; oppilaat; opettajat